The Pine Branch, Spring 1967 - (:unkn) unknown (Valdosta, Ga. : Creative Writing Club of Valdosta State College., 1967)
The Pine Branch. Periodical magazine. Created and published by the Creative Writing Club, English and Art Department, Valdosta State College. Valdosta, Georgia. Includes: editorials, photographs, poems, short stories, and other writings.
Cover Gloria Thompson | Editorial Comment, poem Scott Cohen | Self Realization Gerald Boyd | Sketch Tim Teasley | Photograph Robert Winter | Wild Horses, poem Tim Teasley | Poem Terrence Carter | Sketch Mike Nelson | The Face E H Lightsey | Sketch Sandra Hester | Whispers Elinor Davis | Poems Susanne Evans | Photograph Robert Winter | The Copper Bowl E H Lightsey | Photograph Robert Winter | I See A Misery Larry Long | Sketch Pat Taylor | Modern Concept of the Theatre Stan DeHart | Photograph Billy Orr | Why the Bird, or Why the Bird Tim Teasley | Sketch I Tim Teasley | Inflexibility of an Afternoon Scott Cohen | Sketch Pat Taylor | Sky Tear David Talton | I Sent A Candle by Messenger E H Lightsey | James, James Dana Scouten | The Lover Durrett Bradford | The Raining Sound of Wheels Turning Lynn Smith | Terrible Fear Lynn Smith | Peachtree Creek Ralph Crawford | Photograph Robert Winter | Photograph Robert Winter | Fleeting Friends Tim Teasley | Dear Michael Mike Nelson | Car-Death Relationship,Sketch Tim Teasley | Photograph Robert Winter | Winter E H Lightsey | Sketch Elgin Freeman | Two Photographs Robert Winter | A Need Put Aside Larry Long | Untitled Scott Cohen | Sketch Pat Taylor | Sunday Night Diary E H Lightsey | Sketch Ronald Healan | Sketch Tim Teasley |
Keywords: College publications; College student newspapers and periodicals; Valdosta State University--Periodicals; Valdosta State College; Valdosta; Schools--Georgia; Education